Fast and Selective Post-polymerization Modification of Conjugated Polymers Using Dimethyldioxirane - Reichsöllner, Emmanuel; Creamer, Adam; Cong, Shengyu; Casey, Abby; Eder, Simon; Heeney, Martin; Glöcklhofer, Florian (Frontiers in Chemistry, 2019)
Modification of functional groups attached to conjugated polymer backbones can drastically alter the material properties. Oxidation of electron-donating thioalkyl substituents to electron-withdrawing sulfoxides or sulfones is a particularly effective modification. However, so far, this reaction has not been studied for the modification of conjugated polymers used in organic electronics. Crucial questions regarding selectivity and reaction time waited to be addressed. Here, we show that the reaction is highly selective and complete within just a few minutes when using dimethyldioxirane (DMDO) for the oxidation of thioalkyl substituents attached to the well investigated conjugated polymers poly(9-(1-octylnonyl)carbazole-alt-4,7-dithienylbenzothiadiazole) (PCDTBT) and poly(9,9-dioctylfluorene-alt-benzothiadiazole) (F8BT). The selectivity was confirmed by comparison with polymers obtained from pre-oxidized monomers and by control experiments using related polymers without thioalkyl substituents. Using DMDO, the oxidation yields acetone as the only side-product, which reduces the work-up to mere evaporation of solvents and excessive reagent. Our results show that this oxidation is an exciting method for the preparation of electron-deficient conjugated polymers. It may even allow the preparation of electron acceptors for solar cells directly from the electron donors.